Resource Sharing Strategies for Point-to-Multipoint Distribution in Next-Generation DSL Networks - Mohit Sharma; Marc Moonen; Yannick Lefevre; Paschalis Tsiaflakis (IEEE Open Journal of the Communications Society, 2023)
This paper investigates resource sharing strategies for point-to-multipoint (P2MP) distribution in next-generation digital subscriber line (DSL) networks. The latest DSL ITU standard, multi-gigabit fast access to subscriber terminals (MGfast) or G.9711, supports P2MP transmission as a new feature, which allows resource sharing among multiple customer premises equipments (CPEs). It offers an optimized user experience by efficiently utilizing available resources, thereby reducing the cost of service per user. The resource sharing can be done by allocating part of the available bandwidth to each CPE connected to the same MGfast transceiver unit (MTU-O) at the distribution point unit (DPU). An optimal solution to the grouping and per-group frequency-division multiple access (FDMA) allocation is necessary to optimally exploit the network resources. In this scenario, computing the optimal solutions involves significant computational complexity, especially when the network is dynamic, i.e., CPEs are frequently changing their activity status and traffic demands. Therefore, to overcome these issues, it is necessary to employ heuristic strategies that can provide comparable performance but with significantly reduced computational complexity. This paper proposes the optimal solutions to the grouping and per-group FDMA allocation for both upstream (US) and downstream (DS) P2MP transmission. Additionally, heuristic strategies with significantly lower computational complexity are proposed based on the optimal solutions. These heuristic strategies are shown to achieve comparable performance to the optimal solutions.